How does public debt affect economic growth? A systematic review - Nur Hayati Abd Rahman; Shafinar Ismail; Abdul Rahim Ridzuan (Cogent Business & Management, 2019)
The controversial findings by Reinhart and Rogoff have continuously generated debates on the threshold of debt towards GDP. Hence, the aim of this study is to examine whether there exists mutual consensus on the effects of public debt on the economic growth of a country or group of economies. A systematic review on related articles from SCOPUS database was conducted by adopting a standard procedure in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), namely identification, screening and eligibility. Thirty-three articles were chosen as the main articles to be reviewed. It was found that there is no mutual consensus on the relationship between public debt and economic growth. The relationship can be positive, negative or even non-linear. Besides, the 90% threshold as argued in the Reinhart-Rogoff hypothesis is also not applied across all countries. The findings may help governments and policymakers to design their fiscal policy by investigating how existing debts affect the growth level. Future studies should investigate the effects of public debt on the economic growth in the upper-middle-income economies. These economies were least studied in this context.
Keywords: 650; Public debt; economic growth; systematic review; PRISMA